Brain correlates of emotional prosodic change detection in autism spectrum disorder - Judith Charpentier; Marianne Latinus; Frédéric Andersson; Agathe Saby; Jean-Philippe Cottier; Frédérique Bonnet-Brilhault; Emmanuelle Houy-Durand; Marie Gomot (NeuroImage: Clinical, 2020)
Autism Spectrum Disorder (ASD) is currently diagnosed by the joint presence of social impairments and restrictive, repetitive patterns of behaviors. While the co-occurrence of these two categories of symptoms is at the core of the pathology, most studies investigated only one dimension to understand underlying physiopathology. In this study, we analyzed brain hemodynamic responses in neurotypical adults (CTRL) and adults with autism spectrum disorder during an oddball paradigm allowing to explore brain responses to vocal changes with different levels of saliency (deviancy or novelty) and different emotional content (neutral, angry).Change detection relies on activation of the supratemporal gyrus and insula and on deactivation of the lingual area. The activity of these brain areas involved in the processing of deviancy with vocal stimuli was modulated by saliency and emotion. No group difference between CTRL and ASD was reported for vocal stimuli processing or for deviancy/novelty processing, regardless of emotional content.Findings highlight that brain processing of voices and of neutral/ emotional vocal changes is typical in adults with ASD. Yet, at the behavioral level, persons with ASD still experience difficulties with those cues. This might indicate impairments at latter processing stages or simply show that alterations present in childhood might have repercussions at adult age.